The reunion of two lineages of the Neotropical brown stinkbug in soybean lands in the heart of Brazil - Soares, Patricia Lima (2017)
The rapid pace of conversion of natural areas to agronomic systems is a matter of great concern, and the consequences for conservation and pest management are not yet fully understood. We examined mitochondrial (COI and Cytb) and nuclear (ITS1) gene regions of 21 Euschistus heros populations to investigate the genetic diversity, genetic structure, and the demographic history of this emerging pest of soybean crops in South America. Two deep divergent lineages that separated in the Pliocene (4.5 My) have been found over a wide area. The northern lineage is older, more diverse, and prevalent in the Amazon and Caatinga, while the southern lineage is younger, less diverse, and prevalent in the Atlantic Forest and Chaco biomes. The secondary contact is occurring mainly in the Cerrado, an important agriculture frontier. Euschistus heros populations are expanding in size and range, but are strongly affected by environment variables. Historical changes during the Plio-Pleistocene created significant genetic differentiation between E. heros populations, which differentiated further in several biomes. The present populations are expanding at different rates, mixing highly diverse populations with less-diverse populations in regions of intensive farming. This, individuals adapted to different environmental conditions and to large monocultures might currently be combining into a panmictic and hard-to-control pest population.